The Relationship between Work Culture and Work Environment with Patient Safety in the Surgical Inpatient Room - Laila An-Nur Fitri Abnurama; Aprina Aprina; Giri Udani; Kodri Kodri; Triafini Noviarti (Jurnal Kesehatan, 2026)
Patient safety is a system designed to make patient care safer, including risk assessment, risk identification and management, and incident reporting and analysis. The World Health Organization emphasized in 2020 the need for increased attention to patient safety in hospitals. This study aimed to determine the relationships among patient safety culture, the work environment, and patient safety in the surgical ward of RSUD Jenderal Ahmad Yani, Metro City, Lampung Province, in 2025. This research used a quantitative, analytical, cross-sectional design. The study was conducted from 16 May to 28 May, 2025. The population consisted of 70 nurses working in the surgical ward, with a sample of 52 respondents selected. Data were collected using an observation sheet to assess work culture and questionnaires to measure the work environment and patient safety. Patient safety was treated as the dependent variable. In contrast, work culture and work environment were the independent variables. Data analysis was performed using the chi-square test. The results showed that 29 respondents (55.8%) had good patient safety, 37 respondents (71.2%) had a positive work culture, and 35 respondents (67.3%) experienced a conducive work environment. Statistical analysis indicated a significant relationship between work culture and patient safety (p = 0.001) and between the work environment and patient safety (p = 0.018). In conclusion, work culture and the work environment are significantly associated with patient safety. Hospitals are recommended to strengthen nursing management by fostering a supportive work environment in the surgical ward.